Order of John Tinker - Tinker, John.
Order permitting recruitment of soldiers in the province of New York for service in the British army in the Bahamas.
British army officer and governor of the Bahama Islands.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Great Britain. -- Army -- Colonial forces -- America; Great Britain. -- Army -- Recruiting, enlistment, etc. -- History -- 18th century; Bahamas -- History -- 18th century; New York (State) -- History -- Colonial period, ca. 1600-1775.; Army officers, British; Governors -- Bahamas